2011
DOI: 10.1038/modpathol.2010.168
|View full text |Cite
|
Sign up to set email alerts
|

Clonal X-chromosome inactivation suggests that splenic cord capillary hemangioma is a true neoplasm and not a subtype of splenic hamartoma

Abstract: Splenic hamartoma is a rare tumor-like lesion composed of structurally disorganized red pulp elements. It has been hypothesized that two other splenic lesions, cord capillary hemangioma and myoid angioendothelioma, may fall within the spectrum of splenic hamartoma, simply representing morphological variants. In this study, we compared the vascular and stromal composition of cord capillary hemangioma and myoid angioendothelioma with those of classical hamartoma. In addition, we assessed the clonal vs polyclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…However, the morphological and immunohistochemical characteristics of our case match those of CCH. The benign nature of CCH in this case was supported by the lack of nuclear atypia and the low proliferation index (<5%), consistent with the observation by Chiu et al …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, the morphological and immunohistochemical characteristics of our case match those of CCH. The benign nature of CCH in this case was supported by the lack of nuclear atypia and the low proliferation index (<5%), consistent with the observation by Chiu et al …”
Section: Discussionsupporting
confidence: 91%
“…5 Meanwhile, in 2011, Chiu et al performed clonality analysis of CCH, the results of which supported the true neoplastic nature of CCH, which was different from a hamartoma. 6 CCH is composed of vessels predominantly expressing CD34 and CD31, but not CD8, which is consistent with the expression by capillaries. Few splenic sinuses expressing CD8 and CD31, but not CD34, may exist in CCH.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Capillary hemangioma is classified as a true tumor by the International Society for the Study of Vascular Anomalies (ISSVA) (2; http://issva.org/ content.aspx?page_id=0&club_id=298433&module_ id=152904) but is classified as a pyogenic granuloma (lobular capillary hemangioma) in the World Health Organization (WHO) classification of skin tumors (3). Chiu et al reported that capillary hemangiomas exhibit clonal X-chromosome inactivation and should thus be considered true neoplasms (4). In contrast, cavernous hemangioma is considered a venous malformation by the ISSVA and WHO (2,3).…”
Section: Introductionmentioning
confidence: 99%